GM food systems and their economic impact - Brankov, Tatjana, 1975- (CABI biotechnology series ;, 2018)
This book adopts a methodical approach to provide a novel exploration of the effects of GM crops on global economy, as well as examining the links between GM and food security at global and regional levels. The environmental implications of GM are also considered, by comparing pesticide use and efficiency in GM and non-GM countries.